Efecto de cuatro niveles de zeolita natural, en el cultivo de papa (Solanum tuberosum), en la zona de El Ángel, Cantón Espejo. Provincia del Carchi - Mora Flores, Mónica Alejandra (2011)
This investigating essay Espejo sold off in the zone the canton's his angel himself in the provinces of the Carchi, with evaluating the performance potential of the potato cultivation to natural zeolita's split-level application purpose; Identifying the or natural zeolita's levels that they contribute to (subj) the bigger- performances obtaining of the cultivation and making the treatments's economic analysis under consideration. Fastened Superchola Utilized to the application the potato variety to the ground of the 25; 50; 75 and 100. Utilized him the experimental design once was named Bloques Completos at random with ten treatments and three repetitions, using Tukey's test to the 5. variables evaluated attended : Height from the beginning to the 60; 90 and 120 days after the germination; stems number for plant, tubers number for plant, classified- tubers number according to his diameter and performance for hectare according to his category ( diameter ).